Understanding and Needs of Adolescents in Stunting Prevention: A Qualitative Study Among Adolescents in Guningkidul Regency, Indonesia - Karuniawati, Benny; Respati, Supriyadi Hari; Mulyani, Sri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting is the result of an interaction between lack of nutritional intake and increased nutritional needs, which has an impact on physical growth and cognitive development, as well as increasing the risk of chronic diseases. In Indonesia, the prevalence of stunting in 2023 will reach 20.8%, still far from the target of 14% in 2024. Adolescence is an important phase to build awareness of nutritional status, because adolescents who understand nutrition can prepare themselves for a healthy pregnancy and reduce the risk of stunting in the next generation. Objective: this study aims to explore the understanding and needs of adolescents related to stunting prevention. This study uses a phenomenological approach to explore adolescents' understanding of stunting prevention programs in Gunungkidul Regency, Yogyakarta. The subjects of the study were 12 adolescent girls aged 12-15 years, selected by purposive sampling based on their experiences. Data collection methods include in-depth interviews and Focus Group Discussions (FGD). The validity of the data was obtained through triangulation and checking with informants. The results of FGD and interviews with adolescents identified three categories of needs: knowledge, behavior, and health conditions of adolescents. Limited access to nutritional information and unhealthy lifestyles increase the risk of stunting. The importance of balanced knowledge and clean living behaviors to support adolescent health is emphasized, especially in preventing future health problems. The social and cultural environment plays an important role in shaping adolescent behavior. The provision of easily accessible nutritional information, as well as support from families and communities, is urgently needed to support the role of adolescents in preventing stunting and ensuring their health and that of future generations.